Carbon fiber adsorption filler for ethyl chloroformate production tail gas and preparation method of carbon fiber adsorption filler
By using carbon fiber adsorption filler, the synergistic effect of iron phthalocyanine and polythiophene-polyaniline copolymer films was solved, and the problem of removing phosgene and other harmful substances in the exhaust gas production of ethyl chloroformate was achieved, and efficient adsorption and removal effects were achieved. , reducing resource waste and environmental pollution.
Patent Information
- Application Number
- CN202411769947.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-11
AI Technical Summary
Existing exhaust gas treatment technology cannot completely remove phosgene and other harmful substances in the exhaust gas produced by ethyl chloroformate, resulting in incomplete treatment, waste of resources and environmental pollution.
Carbon fiber adsorption filler is used, which forms a material with high adsorption activity and chemical stability through the synergistic action of iron phthalocyanine and polythiophene-polyaniline copolymer films, and is used to adsorb and remove harmful substances in the exhaust gas.
The removal efficiency of phosgene in the exhaust gas is significantly improved, the adsorption capacity is enhanced, and the recycling of resources is realized through regeneration treatment, solving the problems of incomplete treatment and resource waste.
Smart Images

Figure BDA0005170010610000081 
Figure BDA0005170010610000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tail gas treatment, and in particular to a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate and a preparation method thereof. Background Art
[0002] Ethyl chloroformate is a colorless transparent liquid with a pungent smell. It is flammable, toxic, and corrosive. Its vapor can strongly irritate the eyes, skin, and mucous membranes. Ethyl chloroformate is mainly used to produce chemical products such as medicines and herbicides, such as cefazolin (Pioneer No. 5), tetrazolylacetic acid, and nicosulfuron. In the production process of ethyl chloroformate, phosgene is one of the key raw materials, but usually there is an excess of 5% to 20%. After the reaction is completed, the excess phosgene will be discharged with the tail gas, resulting in a large amount of phosgene and other harmful substances such as hydrogen chloride and carbon monoxide in the tail gas. Phosgene, also known as carbonyl chloride, is a colorless gas with a pungent smell and is highly toxic. Therefore, the tail gas must be specially treated.
[0003] Existing tail gas treatment technologies generally face problems such as incomplete treatment, waste of resources and environmental pollution. For example, the tail gas is passed into a phosgene destruction tower, destroyed with water under the action of a catalyst, and hydrochloric acid is produced as a by-product together with the hydrogen chloride gas in the tail gas. However, due to the relatively low concentration of phosgene in the tail gas, the phosgene in the tail gas cannot be completely removed, and the tail gas treatment is incomplete. Another method is to absorb ethyl chloroformate with ethanol, but the content of the ethyl chloroformate obtained is only about 85%. If it is used for downstream product production, it still needs to be distilled, which consumes a lot of energy. Summary of the invention
[0004] In order to solve the problems mentioned in the above background technology, the present invention provides a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate and a preparation method thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate comprises the following steps:
[0007] Take iron phthalocyanine and add it to N,N-dimethylformamide, stir evenly, immerse it in surface modified carbon fiber under nitrogen protection, heat and keep it warm for reaction. After the reaction is completed, wash it, dry it in an oven at 100-120℃ to constant weight, and then place it in a muffle furnace for high-temperature activation treatment to obtain a carbon fiber adsorption filler for tail gas in the production of ethyl chloroformate.
[0008] Furthermore, the mass ratio of iron phthalocyanine, N,N-dimethylformamide and surface modified carbon fiber is (0.5-0.7):(15-20):(6-9).
[0009] Furthermore, the heating temperature is 80-90° C., and the heat preservation reaction time is 1-2 hours.
[0010] Furthermore, the temperature of the high temperature activation treatment is 300-320° C., and the treatment time is 30-60 min.
[0011] Further, the surface modified carbon fiber comprises the following steps to prepare:
[0012] S1. Add 3,4-ethylenedioxythiophene and aniline to acetonitrile, then add tetrabutylammonium perchlorate as supporting electrolyte, stir evenly, and select an area of 1cm 2 The platinum electrode is washed with deionized water, added into excess ethanol, ultrasonically cleaned for 10-20 minutes, dried for later use, and the ultrasonically cleaned platinum electrode is immersed in the solution, and the electrochemical workstation is turned on for polymerization to obtain a polythiophene-polyaniline copolymer film;
[0013] S2. Scrape the polythiophene-polyaniline copolymer film from the electrode, add it to N,N-dimethylformamide to obtain a coating solution, take carbon fiber (6mm) and place it in excess acetone, ultrasonically clean it for 20-30 minutes, and then wash it with deionized water until there is no acetone residue, immerse the ultrasonically cleaned carbon fiber in the coating solution, and then slowly pull it out to make the coating solution evenly cover the surface of the carbon fiber, place the coated carbon fiber in an oven for heating and curing, and obtain surface modified carbon fiber.
[0014] Furthermore, in step S1, the mass ratio of acetonitrile, 3,4-ethylenedioxythiophene, aniline and tetrabutylammonium perchlorate is (35-40):(6-8):(4-5):(1-2).
[0015] Furthermore, in step S1, the constant potential of the electrochemical workstation is 1.5-1.7 V (vs. Ag / AgCl), the temperature is room temperature, and the polymerization time is 2-3 h.
[0016] Furthermore, in step S2, the immersion time is 10-20 minutes, the curing temperature is 120-130° C., and the curing time is 1-3 hours.
[0017] According to another aspect of the present invention, there is provided a carbon fiber adsorption filler for tail gas from ethyl chloroformate production, which is prepared by the above-mentioned preparation method.
[0018] Beneficial effects of the present invention:
[0019] 1. In the technical solution of the present invention, 3,4-ethylenedioxythiophene and aniline undergo electrochemical oxidative polymerization under constant potential conditions, and the monomer molecules lose electrons on the surface of the platinum electrode to form cationic free radicals, which in turn trigger a chain growth reaction to form a copolymer chain. As the polymerization reaction proceeds, the generated polythiophene-polyaniline copolymer gradually deposits on the electrode surface to form a uniform film with unique doping behavior and good electrochemical reversibility. Subsequently, the carbon fiber is immersed in the coating solution so that the solution is evenly covered on the surface of the carbon fiber. By heating and curing, the copolymer molecular chains form a firm coating layer on the surface of the carbon fiber, and the copolymer molecular chains undergo further cross-linking reactions to enhance the stability and durability of the coating layer. Under nitrogen protection, the iron phthalocyanine molecules are firmly grafted on the surface of the copolymer film through covalent bonds. The introduction of iron phthalocyanine not only enhances the chemical stability of the adsorption filler, but also provides it with higher adsorption activity.
[0020] 2. In the technical solution of the present invention, the surface of the modified carbon fiber has abundant microporous structures and active groups, and has a specific adsorption capacity for harmful substances in the tail gas of ethyl chloroformate production through physical adsorption and chemical adsorption. Physical adsorption is mainly achieved through the capillary action of the microporous structure, while chemical adsorption depends on the chemical reaction between the active groups and the harmful substances.
[0021] 3. In the technical solution of the present invention, the carbon fiber adsorption filler has rich microporous structure and active groups, which can adsorb more harmful substances, thereby improving the adsorption capacity.
[0022] 4. In the technical solution of the present invention, the carbon fiber adsorption filler can restore its adsorption capacity through regeneration treatment such as washing or calcination after adsorption saturation, thereby realizing the recycling of resources. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.
[0025] Preparation Example 1
[0026] The surface modified carbon fiber is prepared by the following steps:
[0027] S1. Add 0.6kg 3,4-ethylenedioxythiophene and 0.4kg aniline to 3.5kg acetonitrile, then add 0.1kg tetrabutylammonium perchlorate, stir evenly, and select an area of 1cm2 The platinum electrode was washed with deionized water, added into 10 kg of ethanol, ultrasonically cleaned for 10 min, dried for later use, and the ultrasonically cleaned platinum electrode was immersed in the solution. The electrochemical workstation was turned on, and the constant potential was 1.5 V (vs. Ag / AgCl). The polymerization was carried out at room temperature for 2 h to obtain a polythiophene-polyaniline copolymer film.
[0028] S2. Scrape 0.5 kg of polythiophene-polyaniline copolymer film from the electrode, add it to 2 kg of N,N-dimethylformamide to obtain a coating solution, take the carbon fiber and place it in excess acetone, ultrasonically clean it for 20 minutes, and then wash it with deionized water until there is no acetone residue, immerse 0.8 kg of ultrasonically cleaned carbon fiber in the coating solution for 10 minutes, and then slowly pull it out to make the coating solution evenly cover the surface of the carbon fiber, place the coated carbon fiber in an oven and heat it at 120°C for 1 hour to obtain surface modified carbon fiber.
[0029] Preparation Example 2
[0030] The surface modified carbon fiber is prepared by the following steps:
[0031] S1. Add 0.7kg 3,4-ethylenedioxythiophene and 0.45kg aniline to 3.8kg acetonitrile, then add 0.15kg tetrabutylammonium perchlorate, stir evenly, and select an area of 1cm 2 The platinum electrode was washed with deionized water, added into 10 kg of ethanol, ultrasonically cleaned for 15 min, dried for later use, and the ultrasonically cleaned platinum electrode was immersed in the solution, the electrochemical workstation was turned on, the constant potential was 1.6 V (vs. Ag / AgCl), and polymerization was carried out at room temperature for 2.5 h to obtain a polythiophene-polyaniline copolymer film;
[0032] S2. Scrape 0.5 kg of polythiophene-polyaniline copolymer film from the electrode, add it to 2 kg of N,N-dimethylformamide to obtain a coating solution, take the carbon fiber and place it in excess acetone, ultrasonically clean it for 25 minutes, and then wash it with deionized water until there is no acetone residue, immerse 0.9 kg of ultrasonically cleaned carbon fiber in the coating solution for 15 minutes, and then slowly pull it out to make the coating solution evenly cover the surface of the carbon fiber, place the coated carbon fiber in an oven and heat it at 125°C for 2 hours to obtain surface modified carbon fiber.
[0033] Preparation Example 3
[0034] The surface modified carbon fiber is prepared by the following steps:
[0035] S1. Add 0.8kg 3,4-ethylenedioxythiophene and 0.5kg aniline to 4kg acetonitrile, then add 0.2kg tetrabutylammonium perchlorate, stir evenly, and select an area of 1cm 2The platinum electrode was washed with deionized water, added into 10 kg of ethanol, ultrasonically cleaned for 20 min, dried for later use, and the ultrasonically cleaned platinum electrode was immersed in the solution. The electrochemical workstation was turned on, and the constant potential was 1.7 V (vs. Ag / AgCl). The polymerization was carried out at room temperature for 3 h to obtain a polythiophene-polyaniline copolymer film.
[0036] S2. Scrape 0.5 kg of polythiophene-polyaniline copolymer film from the electrode, add it to 3 kg of N,N-dimethylformamide to obtain a coating solution, take the carbon fiber and place it in excess acetone, ultrasonically clean it for 20-30 minutes, and then wash it with deionized water until there is no acetone residue, immerse 1 kg of ultrasonically cleaned carbon fiber in the coating solution for 20 minutes, and then slowly pull it out to make the coating solution evenly cover the surface of the carbon fiber, place the coated carbon fiber in an oven and heat it at 130°C for 3 hours to obtain surface modified carbon fiber.
[0037] Example 1
[0038] A method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate comprises the following steps:
[0039] Take 0.05 kg of iron phthalocyanine and add it to 1.5 kg of N, N-dimethylformamide, stir evenly, and immerse it in 0.6 kg of the surface modified carbon fiber prepared in Preparation Example 1 under nitrogen protection, heat it to 80 ° C and keep it warm for 1 hour. After the reaction is completed, wash it, dry it in a 100 ° C oven to constant weight, and then place it in a muffle furnace at 300 ° C for high-temperature activation treatment for 30 minutes to obtain a carbon fiber adsorption filler for tail gas from ethyl chloroformate production.
[0040] Example 2
[0041] A method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate comprises the following steps:
[0042] Take 0.06 kg of iron phthalocyanine and add it to 1.8 kg of N, N-dimethylformamide, stir evenly, and immerse 0.7 kg of surface modified carbon fiber prepared in Preparation Example 2 under nitrogen protection, heat to 85 ° C and keep warm for 1.5 hours. After the reaction is completed, wash, dry in an oven at 110 ° C to constant weight, and then place it in a muffle furnace at 310 ° C for high-temperature activation treatment for 45 minutes to obtain a carbon fiber adsorption filler for tail gas from ethyl chloroformate production.
[0043] Example 3
[0044] A method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate comprises the following steps:
[0045] Take 0.07 kg of iron phthalocyanine and add it to 2 kg of N, N-dimethylformamide, stir evenly, and immerse it in 0.9 kg of surface modified carbon fiber prepared in Preparation Example 3 under nitrogen protection, heat it to 90 ° C and keep it warm for 2 hours. After the reaction is completed, wash it, dry it in a 120 ° C oven to constant weight, and then place it in a muffle furnace at 320 ° C for high-temperature activation treatment for 60 minutes to obtain a carbon fiber adsorption filler for tail gas from ethyl chloroformate production.
[0046] Comparative Example 1
[0047] The difference between this comparative example and Preparation Example 1 is that aniline is not added in step S1, and the remaining steps are the same as those in Preparation Example 1.
[0048] Comparative Example 2
[0049] The difference between this comparative example and Preparation Example 2 is that 3,4-ethylenedioxythiophene is not added in step S1, and the remaining steps are the same as those in Preparation Example 2.
[0050] Comparative Example 3
[0051] The difference between this comparative example and Example 1 is that iron phthalocyanine is not added, and the remaining steps are the same as those of Example 1.
[0052] Comparative Example 4
[0053] The difference between this comparative example and Example 2 is that the surface-modified carbon fiber prepared in Comparative Example 1 is used, and the remaining steps are the same as those in Example 2.
[0054] Comparative Example 5
[0055] The difference between this comparative example and Example 3 is that the surface-modified carbon fiber prepared in Comparative Example 2 is used, and the remaining steps are the same as those in Example 3.
[0056] Comparative Example 6
[0057] The difference between this comparative example and Example 3 is that carbon fiber is used instead of surface-modified carbon fiber, and the remaining steps are the same as those in Example 3.
[0058] 0.5 kg of carbon fiber adsorption filler prepared in Examples 1-3 and Comparative Examples 3-6 were respectively placed in the test container, and a control group was set up, in which only carbon fiber was placed. Take the tail gas produced by ethyl chloroformate, open the gas delivery system, and pass it into each test container in batches for adsorption for 2 hours. Referring to GB 19041-2024 "Safety Specification for the Production of Phosgene and Phosgenation Products", the phosgene concentration in the final tail gas was detected, and the decomposition efficiency of phosgene was calculated. Decomposition efficiency (%) = (phosgene concentration before treatment - phosgene concentration after treatment) / phosgene concentration before treatment. The results are shown in Table 1:
[0059] Table 1. Phosgene treatment results
[0060]
[0061]
[0062] As can be seen from Table 1, the phosgene decomposition efficiency of Examples 1-3 is relatively high, indicating that the surface-modified carbon fiber adsorption filler prepared has a very high removal capacity for phosgene in the tail gas of ethyl chloroformate production, which may be due to the synergistic effect of the polythiophene-polyaniline copolymer film and iron phthalocyanine, providing an effective adsorption and decomposition site for phosgene. Compared with Example 1, Comparative Example 3 did not add iron phthalocyanine, and its decomposition efficiency dropped significantly to 92.07%. Comparative Examples 4-5 used the surface-modified carbon fibers prepared in Comparative Examples 1-2, respectively, and their decomposition efficiency further dropped to 89.75% and 88.80%. Since aniline was not added in Comparative Example 1 and 3,4-ethylenedioxythiophene was not added in Comparative Example 2, the structure of the polythiophene-polyaniline copolymer film may be incomplete, thereby affecting its adsorption and decomposition capacity for phosgene. Comparative Example 6 used unmodified carbon fiber, while the control group only used carbon fiber without any treatment, and the decomposition efficiency was relatively low, indicating that the unmodified carbon fiber had limited adsorption and decomposition capacity for phosgene.
[0063] In summary, the carbon fiber adsorption filler prepared in Examples 1-3 has a high decomposition efficiency for phosgene in the tail gas from the production of ethyl chloroformate.
[0064] In the description of the specification, the description with reference to the terms "preparation example", "embodiment", "various embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or preparation example are included in at least one embodiment or preparation example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or preparation example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or preparation examples in a suitable manner.
[0065] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate, characterized in that: The following steps are involved: Take iron phthalocyanine and add it to N,N-dimethylformamide, stir evenly, immerse it in surface modified carbon fiber under nitrogen protection, heat and keep it warm for reaction. After the reaction is completed, wash it, dry it to constant weight, and then place it in a muffle furnace for high-temperature activation treatment to obtain a carbon fiber adsorption filler for tail gas in the production of ethyl chloroformate.
2. The method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate according to claim 1, characterized in that: The mass ratio of iron phthalocyanine, N,N-dimethylformamide and surface modified carbon fiber is (0.5-0.7):(15-20):(6-9).
3. The method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate according to claim 1, characterized in that: The heating temperature is 80-90°C, and the insulation reaction time is 1-2h.
4. The method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate according to claim 1, characterized in that: The temperature of the high temperature activation treatment is 300-320°C, and the treatment time is 30-60 minutes.
5. The method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate according to claim 1, characterized in that: Surface modified carbon fiber The method comprises the following steps: S1. Add 3,4-ethylenedioxythiophene and aniline to acetonitrile, then add tetrabutylammonium perchlorate, stir evenly, immerse the ultrasonically cleaned platinum electrode in the solution, start the electrochemical workstation for polymerization, and obtain a polythiophene-polyaniline copolymer film; S2. Scrape the polythiophene-polyaniline copolymer film from the electrode, add it to N,N-dimethylformamide to obtain a coating solution, immerse the ultrasonically cleaned carbon fiber in the coating solution, then slowly pull it out, place it in an oven for heating and curing, and obtain surface-modified carbon fiber.
6. The method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate according to claim 5, characterized in that: In step S1, the mass ratio of acetonitrile, 3,4-ethylenedioxythiophene, aniline and tetrabutylammonium perchlorate is (35-40):(6-8):(4-5):(1-2).
7. The method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate according to claim 5, characterized in that: In step S1, the constant potential of the electrochemical workstation is 1.5-1.7 V (vs. Ag / AgCl), the temperature is room temperature, and the polymerization time is 2-3 h.
8. The method for preparing a carbon fiber adsorption filler for tail gas produced by ethyl chloroformate according to claim 5, characterized in that: In step S2, the immersion time is 10-20 minutes, the curing temperature is 120-130° C., and the curing time is 1-3 hours.
9. A carbon fiber adsorption filler for tail gas produced by ethyl chloroformate, prepared by the preparation method according to any one of claims 1 to 8.